Perancangan A'Naden Hotel Sebagai Hotel Bernuasa Taman di Cikarang Timur - Avoressi, Dian Dianti; Dewi, Emmi Rostika; Wulandari, Anna; Ibrahim, Maulana Yusuf (Jurnal Pelita Teknologi, 2021)
Cikarang is currently one of the largest industrial areas in Asia, attracting many visitors from both within the country and abroad. Therefore, commercial buildings are in high demand, considering that many of these visitors require lodging facilities. The purpose of this writing is to serve as a conceptual foundation for designing a garden-themed hotel building in East Cikarang District, making this hotel uniquely attractive with green open spaces applied in the form of gardens to help minimize pollution. To realize this design, various analyses are required. These analyses will form the theoretical basis for this design. The concept applied is analogous to the Biohazard Antivirus symbol, commonly used as a warning to indicate that preventive actions should be taken when exposed to potentially hazardous substances. Based on the analysis, it is concluded that to realize this design, it is necessary to conduct various analyses related to the design of the hotel as the main activity and the garden as a supporting activity in the design. Examining the types of vegetation to be used is also very important in order to minimize pollution caused by the surrounding environment, thereby achieving the design's objectives.